2014
DOI: 10.1387/revpsicodidact.11097
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Preadolescents’ Roles on Bullying, and Its Relation with Social Climate and Parenting Styles // Roles en bullying de adolescentes y preadolescentes, y su relación con el clima social y los estilos educativos parentales

Abstract: Roles en bullying de adolescentes y preadolescentes, y su relación con el clima social y los estilos educativos parentales Fuensanta Cerezo, Consuelo Sánchez, Cecilia Ruiz, y Julián-Jesús Arense Universidad de MurciaResumen En este estudio se analiza la relación entre la dinámica bullying y variables del contexto escolar y familiar y estilos educativos familiares, e indaga en las diferencias según el rol en bullying. La muestra estuvo constituida por 847 estudiantes (450 chicos y 397 chicas), entre 9 y 18 años… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 21 publications
3
22
0
13
Order By: Relevance
“…In this way, hypothesis 1 was supported almost entirely, and the results confirmed the review carried out in international studies. Specifically, similar percentages of victims were found in Bannink et al 2014and ISEI-IVEI (2017), and several studies found similar percentages of bullies involved in face-to-face bullying (Cerezo et al, 2015;Shin et al, 2016). The percentage of bully-victims found in this study is similar to that of Shin et al (2016), who found 25%, but higher than those reported by most studies, which overall reported figures below 15% (García-Fernández et al, 2016;Guilheri et al, 2015), as well as studies that found percentages below 5% (Cerezo et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this way, hypothesis 1 was supported almost entirely, and the results confirmed the review carried out in international studies. Specifically, similar percentages of victims were found in Bannink et al 2014and ISEI-IVEI (2017), and several studies found similar percentages of bullies involved in face-to-face bullying (Cerezo et al, 2015;Shin et al, 2016). The percentage of bully-victims found in this study is similar to that of Shin et al (2016), who found 25%, but higher than those reported by most studies, which overall reported figures below 15% (García-Fernández et al, 2016;Guilheri et al, 2015), as well as studies that found percentages below 5% (Cerezo et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…As can be seen in Table 1, with respect to face-to-face bullying, the percentage of victims ranges from 7% (Cerezo, Sánchez, Ruiz, & Arense, 2015;Navarro, Yubero, & Larrañaga, 2015) to approximately 33% (Blaya & Fartoukh, 2016;Leung & Mcbridge-Chang, 2013;Price, Chin, Higa-McMillan, Kim, & Frueh, 2013). In the case of bullies, the proportion ranges from 4% (Iossi- Silva, Pereira, Mendonça, Nunes, & de Oliveira, 2013;Navarro et al, 2015), to approximately 20% (García-Fernández, Romera-Félix, & Ortega-Ruiz, 2016;Leung & Mcbridge-Chang, 2013;Shujja, Att, & Shujjat, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies emphasize that family environment and parental styles are the main tools available to young people to achieve a correct social adaptation. Regarding the social climate of the family, effective communication allows an appropriate adjustment of adolescents [1,2]. From the Pinquart study [3], we know that the authoritarian, permissive, and neglectful parenting styles are associated with higher levels of externalizing problems, and that victimization and deviant behavior are influenced by negative control [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most research carried out in recent years in Spain [5,6] has investigated bullying and violence in schools among peers, and includes a range of different types of behaviour such as taunts, threats, intimidation, physical aggression and exclusion. These are systematic and an abuse of power of one or more pupils over a defenceless victim, while others are passive observers and do not intervene to prevent the situation [7].…”
Section: Introductionmentioning
confidence: 99%